Artificial Intelligence and the Data Protection Crisis: When the Absent State Faces the Threat of Personal Data Abuse - Afdal Mubarak; Andi Sri Amlinawaty Muin; Aan Aswari (HORIZON PUBLIC LEGAL STUDIES, 2025)
This study aims to find out and analyze the adequacy of laws and regulations in Indonesia in regulating the use of artificial intelligence technology (Artificial Intelligence) that accesses and processes people's personal data. And knowing and formulating the necessary legal remedies to close the regulatory gap for the prevention of the misuse of artificial intelligence (A.I.) on personal data.This research is a normative law research with a legislative and conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal materials that are analyzed prescriptively to explain the applicable legal provisions and provide normative arguments and recommendations. The results of this study indicate that laws and regulations in Indonesia do not specifically regulate the use of Artificial Intelligence that accesses people's personal data. Although the Personal Data Protection Law has provided a legal basis, there is no specific regulation that regulates the characteristics of AI, so the existing regulations are not fully adequate. As well as the legal measures needed to close the regulatory gap to prevent the misuse of personal data, namely, the establishment of the Artificial Intelligence Law, the strengthening and harmonization of existing laws and regulations, the improvement of digital forensic technology, the strengthening of transparency and accountability obligations of AI system operators. As well as strengthening the supervision and law enforcement mechanism